Generating Realistic Fake Equations in Order to Reduce Intellectual Property Theft - Xiong, Yanhai; Ramachandran, Giridhar Kaushik; Ganesan, Rajesh; Jajodia, Sushil; Subrahmanian, V. S. (IEEE transactions on dependable and secure computing, 2022)
According to Symantec, the average gap from the time a company is compromised by a zero-day attack to the time the vulnerability is discovered is 312 days. This leaves an adversary with a lot of time to exfiltrate corporate IP. Recent work has suggested automatically generating multiple fake versions of a document to impose costs on the attacker who needs to correctly identify the original document from a set of mostly fake documents. But in the real world, documents contain many diverse components. In this article, we focus on technical documents that often contain equations. We present {\sf FEE} FEE<inline-graphic xlink:href="jajodia-ieq1-3038132.gif"/> (Fake Equation Engine), a framework to generate fake equations in such documents. {\sf FEE} FEE<inline-graphic xlink:href="jajodia-ieq2-3038132.gif"/> tries to preserve multiple aspects of a given equation when generating a fake. Moreover, {\sf FEE} FEE<inline-graphic xlink:href="jajodia-ieq3-3038132.gif"/> is very general and applies to diverse equational forms including polynomial equations, differential equations, transcendental equations, and more. {\sf FEE} FEE<inline-graphic xlink:href="jajodia-ieq4-3038132.gif"/> iteratively solves a complex, changing optimization problem inside it. We also present {\sf FEE-FAST} FEE-FAST<inline-graphic xlink:href="jajodia-ieq5-3038132.gif"/> , a fast approximate algorithm to solve the optimization problem within {\sf FEE} FEE<inline-graphic xlink:href="jajodia-ieq6-3038132.gif"/> . Using a panel of human subjects, we show that {\sf FEE} FEE<inline-graphic xlink:href="jajodia-ieq7-3038132.gif"/> achieves a high rate in deceiving sophisticated subjects.